Forma, estilo y contexto en la cultura material de la Edad de Bronce gallega : cerámica campaniforme y cerámica no decorada - Prieto Martínez, María Pilar (1998)
"We have carried out an analysis of Galician Bronze Age pottery from a Landscape Archaeology perspective. The analysis, attending as well domestic as funerary context, have included both decorated bell beaker pottery and undecorated pots. As a complement, we have studied some other codes in decorated prehistoric material culture, with the aim of defining the models of organization of decoration and style in that pottery. As well pottery as the other decorated material culture have been analyzed through an alternative procedure to that used in Archaeology up to this moment, the formal analysis, following the pattern of French structural anthropology. The description tool we have used is the Potes Database, formal analysis is based on the Operative Technological Chain and the whole system is covered by the concept of style, understood as a theoretical-methodological, practical and meaningful proposal. The results are centred on the characterization of Bronze Age ceramic style with reference to the context. Once reviewed its long term chronological scope and wide spatial distribution along Europe, we believe that the ceramic style discovered in Galicia becomes significant to the whole Bronze Age social system."